Valuing the Protection Services of Mangroves in the Philippines - Wealth Accounting and the Valuation of Ecosystem Services (Washington, DC: World Bank, 2017)
Mangroves and other coastal ecosystems act as natural defenses to reduce the risks from flooding, erosion and natural disasters. Yet the value of these habitats is often not fully accounted for in policy and management decisions, and thus they continue to be lost at alarming rates. Using natural capital accounting, we can measure and value the services provided by these coastal ecosystems, and thus inform policies for sustainable development, disaster risk reduction, and environmental conservation. A new report measures and values the coastal protection benefits of mangroves in the Philippines.